Construction and validation of the CDE-A19 emotional development questionnaire for emotional education management in teachers - Cabeza-Flores, Elena Juana (2025)
Mental health is one of the main problems of the 21st century worldwide and in Peru, also affecting the education sector. It is estimated that 40.6% of teachers suffer from chronic work-related stress, depression, anxiety and neurological problems, a situation that is exacerbated by the fact that the majority of Peruvian teachers are over 50 years of age. This situation highlights a high psychosocial risk and the need for relevant socio-emotional assessment tools that are adapted to the reality of Peruvian teachers. In this context, the objective of this research was to construct and validate the Adult Emotional Development Questionnaire (CDE-A19), aimed at emotional management in teachers at public educational institutions in UGEL 04 – Comas. The study was conducted with a sample of 167 teachers, aged between 28 and 64, from institutions in the districts of Comas (52.6%) and Carabayllo (47.3%). The questionnaire, consisting of 19 items, underwent content validation using Aiken's V, achieving an overall value of 1.000, which demonstrated high validity in terms of the relevance, clarity and appropriateness of the items. Likewise, confirmatory factor analysis showed an adequate fit of the model (X2/gl = 1.413; SRMR = 0.063; RMSEA = 0.051; CFI = 0.927; TLI = 0.912), confirming its structural validity. Finally, the reliability analysis yielded a Cronbach's alpha coefficient of 0.908, which is considered excellent. It is concluded that the CDE-A19 is valid and reliable for assessing the management of emotional education in public school teachers.